Extrapolating neurogenesis of mesenchymal stem/stromal cells on electroactive and electroconductive scaffolds to dental and oral-derived stem cells - Heng, Boon Chin *; Bai, Yunyang; Li, Xiaochan; Zhang, Xuehui; Deng, Xuliang (Springer Nature, 2022)
The high neurogenic potential of dental and oral-derived stem cells due to their embryonic neural crest origin, coupled with their ready accessibility and easy isolation from clinical waste, make these ideal cell sources for neuroregeneration therapy. Nevertheless, these cells also have high propensity to differentiate into the osteo-odontogenic lineage. One strategy to enhance neurogenesis of these cells may be to recapitulate the natural physiological electrical microenvironment of neural tissues via electroactive or electroconductive tissue engineering scaffolds. Nevertheless, to date, there had been hardly any such studies on these cells. Most relevant scientific information comes from neurogenesis of other mesenchymal stem/stromal cell lineages (particularly bone marrow and adipose tissue) cultured on electroactive and electroconductive scaffolds, which will therefore be the focus of this review. Although there are larger number of similar studies on neural cell lines (i.e. PC12), neural stem/progenitor cells, and pluripotent stem cells, the scientific data from such studies are much less relevant and less translatable to dental and oral-derived stem cells, which are of the mesenchymal lineage. Much extrapolation work is needed to validate that electroactive and electroconductive scaffolds can indeed promote neurogenesis of dental and oral-derived stem cells, which would thus facilitate clinical applications in neuroregeneration therapy.